Drying kinetics of nectarine slices in a heat pump drying system - Tunckal, Cuneyt; Direk, Mehmet; Doymaz, Ibrahim (TAYLOR & FRANCIS INC, 2024)
This study focused on investigating the drying behaviors of nectarine slices under varying drying temperatures (Tdrying) through the utilization of energy and exergy analysis methodologies, alongside an exploration of the drying kinetics employing diverse mathematical models. The drying process was carried out using a closed-type heat pump drying (HPD) system. The findings revealed a reduction in drying time with an increase in temperature. Notably, the condenser, compressor, and drying cabinet exhibited their highest exergy efficiencies at a Tdrying of 45 degrees C, while the evaporator demonstrated its highest exergy efficiency at 35 degrees C. The highest exergy efficiencies were achieved at a Tdrying of 45 degrees C and calculated as 65.94%, 77.95% and 80.53% for the condenser, dryer and compressor, respectively. Among the considered models, Aghbashlo et al. demonstrated the most optimal fit for moisture ratio. The Deff values ranged from 5.476 x 10-10 to 1.095 x 10-9 m2/s within the Tdrying range of 35 to 45 degrees C. As the Tdrying elevated, the Deff also raised. Using an Arrhenius-type equation, the expression for the temperature dependence of Deff was established. The determined activation energy value for moisture diffusion was 56.50 kJ/mol.
Keywords: Activation; COP; drying kinetics; energy; exergy; moisture diffusion; HOT-AIR; EXERGY ANALYSIS; PERFORMANCE; MICROWAVE; QUALITY; DRYER; Energy & Fuels; Engineering; Environmental Sciences & Ecology